2020
DOI: 10.3390/brainsci11010033
|View full text |Cite
|
Sign up to set email alerts
|

A Bibliometric Insight of Genetic Factors in ASD: Emerging Trends and New Developments

Abstract: Autism spectrum disorder (ASD) cases have increased rapidly in recent decades, which is associated with various genetic abnormalities. To provide a better understanding of the genetic factors in ASD, we assessed the global scientific output of the related studies. A total of 2944 studies published between 1997 and 2018 were included by systematic retrieval from the Web of Science (WoS) database, whose scientific landscapes were drawn and the tendencies and research frontiers were explored through bibliometric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 64 publications
(39 reference statements)
0
8
0
Order By: Relevance
“…The retrieved literature was provided by 34 countries/regions, and cooperation modes were observed among major countries and regions ( Figure 5 ). The number of publications published in a country or region is a sensitive indicator, reflecting the degree of concern and research intensity of a particular research field [ 25 ]. In this respect, the United States cooperated closely with other countries/regions and participated in most of the research, with 213 publications and an H-index of 31 ( Table 4 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The retrieved literature was provided by 34 countries/regions, and cooperation modes were observed among major countries and regions ( Figure 5 ). The number of publications published in a country or region is a sensitive indicator, reflecting the degree of concern and research intensity of a particular research field [ 25 ]. In this respect, the United States cooperated closely with other countries/regions and participated in most of the research, with 213 publications and an H-index of 31 ( Table 4 ).…”
Section: Resultsmentioning
confidence: 99%
“…Some people think that many sources may indicate that the authors or documents have attracted the attention of researchers in specific fields [ 24 ]. In recent years, some studies have been conducted from the bibliometrics perspective: research on genetic factors in ASD [ 25 ], robot intervention research [ 26 ], education research [ 27 , 28 ], executive function research [ 29 ], virtual reality research [ 30 ], and a scientific research overview [ 31 ] were reviewed and analyzed. Specifically, Perez-Vazquez, E et al found, by analyzing the literature published between 2005 and 2017, that robots may help autistic children to experience real interactions in the future, but its methodological limitations will hinder the popularization of the research results in this field [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…ASD is the hot spot of current research, and there are some related relevant bibliometric articles. However, previous studies on bibliometrics of ASD mostly focused on a specific field or used a single software ( 15 – 17 ). Therefore, this study used CiteSpace and VOSviewer, combined with bibliometric methods, systematically evaluate the articles on ASD research in the Web of Science (WoS) from 1998 to 2021, focusing on the publishing trend, authors, institutions, countries, published journals, cited articles, research keywords, keywords about etiology and diagnostic markers, and keywords with the strongest citation bursts detection in this research field.…”
Section: Introductionmentioning
confidence: 99%
“…Among the keywords with the strongest burst citation, the “designer drug” burst since 2012 indicates another option of synthetic cathinones compared with traditional Catha edulis ( Karila et al, 2015 ; Wang et al, 2020 ). Compared with mild stimulants used for better concentration and performance during trading, farming, socialization, and leisure activities, heavy use and/or concomitant abuse of substances (poly-drug use behavior, such as Catha edulis and a designer drug) due to stronger psychostimulatory desire is rapidly growing ( Ali, 2018 ).…”
Section: Discussionmentioning
confidence: 99%